2013
DOI: 10.1590/0074-0276108062013018
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic infection in individuals from the municipality of Barcelos (Brazilian Amazon) is not associated with the anti-Plasmodium falciparum glycosylphosphatidylinositol antibody response

Abstract: Anti-glycosylphosphatidylinositol (GPI) antibodies (Abs) may reflect and mediate, at least partially, anti-disease immunity in malaria by neutralising the toxic effect of parasitic GPI. Thus, we assessed the anti-GPI Ab response in asymptomatic individuals living in an area of the Brazilian Amazon that has a high level of malaria transmission. For comparative purposes, we also investigated the Ab response to a crude extract prepared from Plasmodium falciparum, the merozoite surface protein (MSP)3 antigen of P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(36 reference statements)
0
4
1
Order By: Relevance
“…However, an alternative and more tempting interpretation is that this Ab response is being boosted by the increasing quantities of P. falciparum GPI released in the circulation as the parasitemia level grows (Figure 1). 11 Hence, our findings do not support the hypothesis that anti-GPI antibodies mediate clinical (antidisease) immunity against malaria, but are in accordance with those of Boutlis et al 12 and Cissoko et al 13 These authors also failed to detect a relationship between anti-GPI Ab and asymptomatic infections, but, similarly to us, observed a relationship between these Ab and parasitemia levels in infected individuals from Mali and Papua New Guinea.…”
Section: Introductioncontrasting
confidence: 80%
See 2 more Smart Citations
“…However, an alternative and more tempting interpretation is that this Ab response is being boosted by the increasing quantities of P. falciparum GPI released in the circulation as the parasitemia level grows (Figure 1). 11 Hence, our findings do not support the hypothesis that anti-GPI antibodies mediate clinical (antidisease) immunity against malaria, but are in accordance with those of Boutlis et al 12 and Cissoko et al 13 These authors also failed to detect a relationship between anti-GPI Ab and asymptomatic infections, but, similarly to us, observed a relationship between these Ab and parasitemia levels in infected individuals from Mali and Papua New Guinea.…”
Section: Introductioncontrasting
confidence: 80%
“…Our group also evaluated the association between anti-GPI Ab response and development of clinical malaria 11 by comparing the incidence of these antibodies, in supposedly immune asymptomatic carriers of plasmodial infection living in an area of the Brazilian Amazon (Barcelos) with high transmission rates of malaria, with controls with no infection or previous history of malaria from the same area and Angolan (Lubango) patients with symptomatic disease. Our data indicated that the Ab response against P. falciparum GPI was not associated with falciparum asymptomatic infection in individuals chronically exposed to malaria in the Brazilian Amazon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptomatic and or paucisymptomatic infections by P. falciparum and Plasmodium vivax were detected in epidemiological studies in the states of Rondônia (RO) and Amazonas, which likely indicates a pattern of clinical immunity in both populations. [24][25][26][27][28] Seropidemiological studies investigating the type of immune responses elicited in naturally exposed populations to several malaria vaccine candidates in Brazilian populations provide important information on whether immune responses specific to these antigens are generated in natural infections and their immunogenic potential as vaccine candidates.…”
Section: Introductionmentioning
confidence: 99%
“…PfGPI-specific antibodies are found in adults of malaria-endemic areas, and may be inhibiting the ability of PfGPI to induce the hyper-inflammatory response associated with severe malaria. This is still up for debate, since studies that find an association between PfGPI-specific antibody titer and protection from severe malaria (Brasseur et al, 1990 ; Naik et al, 2000 ; Gowda, 2002 ; Keenihan et al, 2003 ; Perraut et al, 2005 ) are balanced by studies that find no such association (de Souza et al, 2002 ; Boutlis et al, 2005 ; Cissoko et al, 2006 ; Gomes et al, 2013 ; Mbengue et al, 2016 ). However, PfGPI-specific antibodies are reported to show relevant action in modulating immune responses by protecting immune cells against severe P. falciparum- induced inflammatory responses in-vitro (Schofield et al, 1993 ; de Souza et al, 2010 ).…”
Section: Exploiting Carbohydrate Antigens For Protozoan Parasite Vaccmentioning
confidence: 99%